GENETIC EVALUATION FOR MORPHOLOGICAL TRAITS OF CORIANDRUM SATIVUM GROWN UNDER SALT STRESS - Aftab, A; Haider, MA; Ali, Q; Malik, A (Biological and Clinical Sciences Research Journal, 2021)
The Coriandrum is most important among the herb which is used as an ingredient in daily human food. It contains a good amount of antioxidants and health improving ingredients that save human body cells from diseases. It is very sensitive for abiotic environmental stress conditions involving drought, heat, and salt stress as important stress conditions. For this purpose, a study was planned to conduct in the greenhouse of the Institute of Molecular Biology and Biotechnology, University of Lahore to determine the effects of salt stress on Coriandrum seedling growth. For our study we have selected four Coriandrum varieties viz., GAMZE, EAGLE, SUPER XO, and PAK-ORG. The results revealed that there were significant differences among the treatments of NaCl concentrations, Coriandrum genotypes, and the interactions among the Coriandrum genotypes and salt concentrations applied. The average Coriandrum seedling length was recorded as 23.021±1.2026cm while root length was recorded as 22.0128±1.0027cm. The genotype GAMZE showed higher root and shoot length which indicated that GAMZE was a higher salt-tolerant genotype and may be used as a salt-tolerant genotype to improve yield per plant in Coriandrum. The genotype EAGLE has shown poor performance for all of the studied traits which indicated that it was a salt-sensitive Coriandrum genotype. The genetic advance and heritability were found higher for all of the studied traits. The significant correlation between shoot length and root length indicated that the genotypes grow longer roots under stress conditions to increase the shoot length of plants while survive under stressful environmental conditions. The selection of Coriandrum genotype on the basis of root length and shoot length may be useful to improve slat stress tolerance in Coriandrum genotypes for higher seed and green plant biomass yield.